Mokken analysis of the Health of the Nation Outcome Scales in acute inpatient and community samples. (October 2016) - Muncer, Steven; Bass, Malcolm; Dawkin, Matt
Objective: The structure and scoring of the Health of the Nation Outcome Scales (HoNOS) has been open to debate. Most studies have relied on factor analytic approaches to investigate HoNOS structure. Our aim is to investigate HoNOS using methods from item response theory. Methods: Completed HoNOS forms from patients receiving mental health treatment in the community and also inpatients were subjected to Mokken analysis, which is a non-parametric form of item response theory. Confirmatory factor analysis was then used to investigate these scales. Results: Two scales with the same items were found in both samples; however, the inpatient sample scored higher on both scales. The first scale contained three items (10, 11, 12) from the social scale, and the other was related to depression (2, 7, 8). Confirmatory factor analysis showed that a two scale structure had better fit statistics than other suggested structures. Conclusions: HoNOS might best be conceived as two scales measuring aspects of social adjustment and depression.